Retrosternal goitre associated with chylothorax: case report - Bławat, Przemysław; Kowalewski, Janusz; Dancewicz, Maciej; Bella, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Retrosternal goitre is a very unusual cause of chylothorax. Until now, to our knowledge, only seven such cases have been reported. In this article, we describe a case of right chylothorax associated with superior vena cava syndrome in a 75-year-old female patient. The above-mentioned symptoms were caused by retrosternal goitre. Chylothorax lasting many days caused a cough and dyspnoea in the patient and a giant mediastinal tumour caused compression of the superior vena cava and displacement of the trachea and aortic arch vessels. The cause of chylothorax was confirmed clinically by no retention of chy- le in pleural space after radical excision of thyroid adenoma. After surgical removal, symptoms of superior vena cava syndrome decreased progressively. This case is discussed in the context of the topic described in the literature.